2017
DOI: 10.24200/sci.2017.2376
|View full text |Cite
|
Sign up to set email alerts
|

Application of damage spectra as seismic intensity measures in Endurance Time method for steel moment-resisting frames

Abstract: Abstract. In seismic resistant design of moment frames, the structure behavior under earthquakes has to be examined considering various damage criteria. Damage indices can be estimated by Endurance Time (ET) method with minimum computational e ort. The quality of this estimation can be improved in di erent ways. In this paper, the graphs of a certain damage index versus natural period of the structure, called damage spectra, are produced applying intensifying ET records and scaled Ground Motions (GM). Then, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Mainly, the Endurance Time Method represents a promising approach to seismic investigation, providing valuable information for the design and retrofitting of structures to improve their seismic performance. Its unique ability to identify critical points in a structure's response can help engineers and researchers develop more effective seismic-resistant systems (Estekanchi et al,2007;Basim and Estekanchi, 2015;Maleki-Amin and Estekanchi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mainly, the Endurance Time Method represents a promising approach to seismic investigation, providing valuable information for the design and retrofitting of structures to improve their seismic performance. Its unique ability to identify critical points in a structure's response can help engineers and researchers develop more effective seismic-resistant systems (Estekanchi et al,2007;Basim and Estekanchi, 2015;Maleki-Amin and Estekanchi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Their results reported that input motions of the ET method, generated based on a design response spectrum can be used to assess frames at different seismic hazard levels correctly. Maleki-Amin and Estekanchi [14] evaluated various damage indices of a steel moment frame at two hazard levels via nonlinear time-history analyses of the structure under scaled earthquakes and ET records. They observed that in steel moment-resisting frames, the frame damage estimation can be improved by modifying the target time of ET records based on damage spectra.…”
Section: Introductionmentioning
confidence: 99%